Sharenting, Digital Communication, and Social Recognition Among Mothers Living in Structural Poverty at The Bantargebang Landfill - Dian Sukmawati; Asima Oktavia Sitanggang; Annisa Eka Syafrina (Mediator: Jurnal Komunikasi, 2026)
Sharenting practices are increasingly discussed. Research in Indonesia has mostly focused on urban middle-class families, while studies on low-income families remain limited. This study examines how poverty shapes mothers’ understanding of sharenting, digital literacy, and children’s privacy in everyday life. The Bantargebang Landfill in Bekasi was selected because it reflects poverty, environmental problems, and social marginalization. Using a qualitative case study approach, this research involved in-depth interviews with seven mothers. The findings show that sharenting is not only about sharing family content online, but also about seeking social recognition and responding to poverty stigma. Mothers in scavenger settlements use sharenting to display dignity and equality, while those with more stable economic conditions use social media more strategically for visibility and economic opportunities. The study also finds that digital literacy is practiced pragmatically, with privacy concerns focused mainly on immediate risks rather than children’s long-term digital identity and privacy rights. Using Communication Privacy Management Theory and Recognition Theory, this study highlights the connections among sharenting, privacy management, social recognition, and everyday poverty, emphasizing the need for more context-sensitive digital literacy and child protection programs for marginalized urban families.